Productivity, essential oil variability and antioxidant activity of Ferula assa-foetida L. oleo-gum-resin during the plant exploitation period. Issue 6 (1st November 2020) - Karimian, Vahid; Sepehry, Adel; Barani, Hossein; Ebrahimi, Samad Nejad; Mirjalili, Mohammad Hossein
ABSTRACT: In the present study, productivity, essential oil variability and antioxidant activity of Ferula assa-foetida oleo-gum-resin (OGR) collected at different collection times (July, August, September, and October) were studied by using GC-FID-MS and DPPH assay. The amount of OGR (g/plant) and its oil content significantly affected by the collection time. The highest and the lowest amount of OGR was obtained in September (13.2 g) and July (6.3 g), respectively. The essential oil content (w/w %) was in the order of: July (9.1%)> August (8.2%)> September (7.8%)> October (7.4%). The total number of constituents was 47 in July, 47 in August, 43 in September and 44 in October, representing 97.7%, 98.6%, 96.8%, and 96.8% of the total oil, respectively. α-Pinene (18.2–48.6%), ( Z )-propenyl sec-butyl disulfide (9.4–28.8%), β-pinene (6.2–11.5%), bicyclogermacrene (3.3–6.4%), ( E )-propenyl sec-butyl disulfide (1.3–5.8%), germacrene D (2.0–3.9%) and ( Z )-β-ocimene (1.1–3.6%) were the main components of the OGR oils. The highest radical scavenging (IC50 87.3 ± 5.1 μg/ml) of the collected OGRs was obtained in August.